2020
DOI: 10.1186/s12889-020-09736-9
|View full text |Cite
|
Sign up to set email alerts
|

Mediation effect of body mass index on the association between spicy food intake and hyperuricemia in rural Chinese adults: the Henan rural cohort study

Abstract: Background The relationship of spicy food intake with hyperuricemia remains unknown. The objective of this study was to examine the association between spicy food intake and hyperuricemia, and whether this association was mediated by body mass index (BMI) in Chinese rural population. Methods 38, 027 adults aged 18–79 years were recruited from the Henan Rural Cohort Study. Information on spicy food intake was obtained using a validated questionnaire survey. Multivariable logistic regression model was used to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…In line with previous studies, participants who consumed spicy food more frequently were more likely to be young, a man, current smokers, alcohol drinkers, and have higher BMI and total energy intake ( 36 39 ). We found that both frequency and degree of pungency in spicy food were positively associated with the prevalence of hyperuricemia as well as the serum uric acid level, which was consistent with the results of the Henan rural cohort study ( 29 ). Many previous studies can support our results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with previous studies, participants who consumed spicy food more frequently were more likely to be young, a man, current smokers, alcohol drinkers, and have higher BMI and total energy intake ( 36 39 ). We found that both frequency and degree of pungency in spicy food were positively associated with the prevalence of hyperuricemia as well as the serum uric acid level, which was consistent with the results of the Henan rural cohort study ( 29 ). Many previous studies can support our results.…”
Section: Discussionsupporting
confidence: 90%
“…Besides the essential demographic characteristics including age, sex, educational level, marital status, and annual family income, the following variables that may affect the prevalence of hyperuricemia were explored in the current study: smoking status, alcohol consumption, physical activity, total energy intake, dietary pattern, body mass index (BMI), hypertension, type 2 diabetes mellitus, and dyslipidemia. All the introduced covariates were selected with reference to other studies on the association between spicy food and metabolic diseases ( 23 25 , 29 ). Daily consumption of alcohol (grams of pure alcohol per day) was calculated based on the reported frequency and quantity of drinking.…”
Section: Methodsmentioning
confidence: 99%
“…In line with previous studies, participants who consumed spicy food more frequently were more likely to be young, a man, current smokers, alcohol drinkers, and have higher BMI and total energy intake (36)(37)(38)(39). We found that both frequency and degree of pungency in spicy food were positively associated with the prevalence of hyperuricemia as well as the serum uric acid level, which was consistent with the results of the Henan rural cohort study (29). Many previous studies can support our results.…”
Section: Discussionsupporting
confidence: 92%
“…Besides the essential demographic characteristics including age, sex, educational level, marital status, and annual family income, the following variables that may affect the prevalence of hyperuricemia were explored in the current study: smoking status, alcohol consumption, physical activity, total energy intake, dietary pattern, body mass index (BMI), hypertension, type 2 diabetes mellitus, and dyslipidemia. All the introduced covariates were selected with reference to other studies on the association between spicy food and metabolic diseases (23)(24)(25)29). Daily consumption of alcohol (grams of pure alcohol per day) was calculated based on the reported frequency and quantity of drinking.…”
Section: Assessment Of Covariatesmentioning
confidence: 99%
“…Model 3 was the same as model 2 with additional adjustments for education level, PIR, hypertension, diabetes, smoking, alcohol use, physical activity, CVD, lipid-lowering drug use, hsCRP, eGFR and UCr. Model 4 (fully adjusted model) was adjusted for model 3 plus BMI (both continuous and categorical [< 25, 25–29.9, or ≥ 30 kg/m 2 ] variables) to further adjust for the possible influence of BMI with reference to published methods [ 35 , 36 ]. We conducted linear regression analysis twice using U-Ni as continuous (log 2 -transformed) and categorical (quartiles) variables respectively.…”
Section: Methodsmentioning
confidence: 99%